How to avoid the formation of hazardous chlorates and perchlorates during electro-disinfection with diamond anodes?. (1st July 2020) - Isidro, J.; Brackemeyer, D.; Sáez, C.; Llanos, J.; Lobato, J.; Cañizares, P.; Matthée, T.; Rodrigo, M.A.
Abstract: This work focuses on disinfection of water using electrolysis with diamond coatings avoiding or minimizing the formation of hazardous chlorates and perchlorates using a special type of commercial cells designed by CONDIAS (Itzehoe, Germany) in two different sizes: the CabECO and the MIKROZON cells. In these cells, the electrolyte that separates the anode and cathode is a proton exchange membrane. This helps to minimize the production of perchlorate and this behavior is enhanced in the smallest cell for which the very low contact times between the electrodes and the water allows to avoid the production of perchlorates when operating in a single-pass mode, which becomes a really remarkable point. In this paper, we report tests in which we demonstrate this outstanding performance and we also explain the differences observed in the two cells operating with the same water. Graphical abstract: Image 1 Highlights: Cell design is a decisive point for electro-disinfection with diamond electrodes. Pathogens removed by several log orders with low electric charges. Chlorates and perchlorates produced in disinfection prevented with cell design. Great significance of hydraulic residence time on the production of chlorates.